2005
DOI: 10.1021/ie049475f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Small Amounts of Additives on Gas Hold-Up, Bubble Size, and Interfacial Area

Abstract: The gas-liquid interfacial area, which is determined by the gas hold-up and the Sauter mean bubble diameter, determines the production rate in many industrial processes. The effect of additives on this interfacial area is, especially in multiphase systems (gas-liquid-solid, gasliquid-liquid), often not understood. The addition of a third phase can cause the gas-liquid system to become completely opaque, which means that conventional techniques to study the interfacial area cannot be used. For this reason ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
2
10
0
2
Order By: Relevance
“…The specific area lack of sensitivity to organic holdup agrees with data obtained by Cents et al (2005) in a bubble column, both for spreading and non-spreading Das et al (1985), who found specific area to initially increase as toluene (spreading) holdup increased, go through a maximum at around 10% holdup, and then decrease, leading to depression of a at high holdup of toluene. Correia et al (2010) also found significant variation of specific interfacial area with holdup of a non-spreading organic phase.…”
Section: Resultssupporting
confidence: 88%
“…The specific area lack of sensitivity to organic holdup agrees with data obtained by Cents et al (2005) in a bubble column, both for spreading and non-spreading Das et al (1985), who found specific area to initially increase as toluene (spreading) holdup increased, go through a maximum at around 10% holdup, and then decrease, leading to depression of a at high holdup of toluene. Correia et al (2010) also found significant variation of specific interfacial area with holdup of a non-spreading organic phase.…”
Section: Resultssupporting
confidence: 88%
“…The gas hold-up increases slighter than the Sauter mean diameter behaviour, previously commented, and this fact explains the behaviour shown in Figure 6 for interfacial area. In the analysis of the gas flow-rate influence upon gas-liquid interfacial area, the higher values correspond to high gas flow-rates, and this behaviour is in agreement with the most common behaviour found in literature [26,27]. An increase in gas flow-rate produces large bubbles (see Figure 4), but also a high gas hold-up.…”
Section: Methodssupporting
confidence: 89%
“…Vedaiyan et al (41) proposed an empirical correlation for the calculation of the Sauter drop diametar, given by: [18] where: u 0 -superficial velocity of the dispersed phase at the nozlle, d 0 -diameter of the nozlle of the distributor of dispersed phase. The influence of different additives (1-octanol; dodecane, and toluene) on the interfacial area was studied in a stirred vessel and in a bubble column under coalescing and noncoalescing conditions (42). The effect of additives on this interfacial area is often not undrestood, especially in multiphase systems (gas-liquid-solid, gas-liquid-liquid).…”
Section: Drop Size and Interface Areamentioning
confidence: 99%